Pengaruh Profitabilitas, Pertumbuhan Laba, Dan Struktur Modal Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility Sebagai Variabel Moderasi - Nathasia Anggi Amelia; Saiful Anwar (Universitas Pendidikan Ganesha, 2022)
The value is the aftereffect of the organization's monetary exhibition in one period. The rationale for this review is to examine the impact of benefits, benefit development, and capital construction on firm value and to examine the capacity of corporate social obligations to direct the impact of productivity, benefit development, and capital design on firm value in the buyer cycle. regional organizations listed on the Trade Exchange. Indonesia 2015-2019.The sampling technique used a purposive testing strategy using specific steps to obtain 24 organizations with 120 annual reports. The investigative strategy used is Partial Least Square using WarpPLS 7.0 software.The results of this study indicate that benefits affect firm value, while benefit development and capital design have no impact on firm value. Furthermore, the existence of corporate social obligations as a driving variable weakens the impact of benefit development on firm value, but cannot direct the impact of productivity and capital construction on firm value.